Wheat Blast: Past, Present, and Future - Ceresini, Paulo Cezar [UNESP]; Castroagudin, Vanina Lilian [UNESP]; Rodrigues, Fabricio Avila; Rios, Jonas Alberto; Aucique-Perez, Carlos Eduardo; Moreira, Silvino Intra; Alves, Eduardo; Croll, Daniel; Nunes Maciel, Joao Leodato; Leach, J. E.; Lindow, S. E. (Annual Reviews, 2018)
The devastating wheat blast disease first emerged in Brazil in 1985. The disease was restricted to South America until 2016, when a series of grain imports from Brazil led to a wheat blast outbreak in Bangladesh. Wheat blast is caused by Pyricularia graminis-tritici (Pygt), a species genetically distinct from the Pyricularia oryzae species that causes rice blast. Pygt has high genetic and phenotypic diversity and a broad host range that enables it to move back and forth between wheat and other grass hosts. Recombination is thought to occur mainly on the other grass hosts, giving rise to the highly diverse Pygt population observed in wheat fields. This review brings together past and current knowledge about the history, etiology, epidemiology, physiology, and genetics of wheat blast and discusses the future need for integrated management strategies. The most urgent current need is to strengthen quarantine and biosafety regulations to avoid additional spread of the pathogen to disease-free countries. International breeding efforts will be needed to develop wheat varieties with more durable resistance.
Keywords: fungal infection; host physiology; integrated disease management strategies; international quarantine; wheat blast origin; pathogen diversification; population biology; epidemiology; Pyricularia graminis-tritici